PENGARUH CAPACITY BUILDING PADA PEMAHAMAN PRINSIP GOOD GOVERNANCE DALAM MENINGKATKAN KINERJA APARATUR - Darwanis, Darwanis; Aliamin, Aliamin; Amrullah, Mohammad (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 10 No 1 (2015))
The purpose of this research was to analyze the impact of capacity building, government staffs’performance and the application of good governance toward local state financial management effectivity at Kabupaten Bireuen. Responden of the research were Local State Financial Officers (PPK), Budget Staffs (PA), Budget Allocation Staffs (KPA) and Treasurees at 24 Local State Government Units (SKPK) Kabupaten Bireuen. Data collected in this research processed using LISREL (Linear Structural RELationship) 8.7 software and Structural Equation Modelling (SEM) were used to analyzed the information needed from the data.The result of the research indicated both simultaniously and partially capacity building affected the understanding of good governance principles, government staffs’performance and the application of good governance local state financial effectivity at Kabupaten Bireuen. The result were also indicated that partially capacity building unaffected the financial effectivity.
Keywords: capacity building, good governace principles government staffs’performance, local state financial management effectivity